Is There a Role of Radiotherapy in the Management of Pancreatic Neuroendocrine Tumors (PNET)? - Saif, Muhammad Wasif; Ng, John; Chang, Bryan; Russo, Suzanne (JOP. Journal of the Pancreas, 2012)
Pancreatic neuroendocrine tumors (PNET) represent a heterogeneous group of tumors with varying tumor biology and prognosis. Advanced PNETs remain a difficult therapeutic challenge because of their high malignant potential and their resistance to conventional chemotherapy although there have been recent developments with promising results with the use of novel agents for the treatment of this disease. Combined modality chemoradiation is not widely used in the management of locally advanced pancreatic endocrine tumors. We discuss Abstract #335 from 2012 ASCO GI Cancers Symposium and share our experience to discuss efficacy and toxicity of concurrent capecitabine or infusional 5-fluorouracil and radiotherapy in patients with resected, locally advanced and metastatic PNET. Prospective studies to investigate the role of radiation and chemoradiation are warranted.